Simulation-Based Optimization (Parametric Optimization Techniques and Reinforcement Learning) - Gosavi, Abhijit (Springer, 2015)
This book is written for students and researchers in the field of indus trial engineering, computer science, operations research, management science, electrical engineering, and applied mathematics. The aim is to introduce the reader to a subset of topics on simulation-based op timization of large-scale and complex stochastic (random) systems. Our goal is not to cover all the topics studied under this broad field. Rather, it is to expose the reader to a selected set of topics that have recently produced breakthroughs in this area. As such, much of the material focusses on some of the key recent advances...